2022
DOI: 10.3390/ijerph191710723
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Static Balance Impairment and Associated Factors of University Student Smartphone Users with Subclinical Neck Pain: Cross-Sectional Study

Abstract: The aim of this study was to assess the prevalence of static balance impairment in university student smartphone users with subclinical neck pain and identify the associated risk factors. Because of rapid and widespread smartphones use, and the subsequent effect on neck pain in university students, it is essential to determine the prevalence of balance impairment and associated factors in this population. Simple random sampling was completed among eighty-one participants in this cross-sectional study. A self-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 76 publications
0
10
0
1
Order By: Relevance
“…Eleven studies [ 30 , 32 , 36 , 37 , 41 , 43 , 47 , 49 , 53 , 56 , 57 ] analyzed the impact of a long-time electronic product used daily on neck pain in 10,314 college students. The results of the combined meta-analysis demonstrated that prolonged use of electronics was significantly associated with neck pain in college students (OR = 1.53, 95% CI: 1.33 to 1.76, P < 0.00001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven studies [ 30 , 32 , 36 , 37 , 41 , 43 , 47 , 49 , 53 , 56 , 57 ] analyzed the impact of a long-time electronic product used daily on neck pain in 10,314 college students. The results of the combined meta-analysis demonstrated that prolonged use of electronics was significantly associated with neck pain in college students (OR = 1.53, 95% CI: 1.33 to 1.76, P < 0.00001).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have revealed that total daily electronic product use of ≥ 3 h and a long time to bow your head ≥ 1 h is likely to lead to neck pain [ 12 , 30 , 33 , 36 , 40 , 43 , 45 , 47 , 56 , 57 ] . Therefore, with the increased use of electronic products and the academic burden, the prevalence of neck pain among college students is also increasing.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 17 full-text articles were assessed for eligibility, and 10 were excluded. Finally, 7 studies [9, [13][14][15][16][17][18] with a total of 10,715 participants were included in the systematic review and meta-analysis.…”
Section: Study Selectionmentioning
confidence: 99%
“…In this study, waist pain was connected to the size of the LCD screen. Smartphone use was negatively associated with leg and foot pain;20 however, there was no connection between LCD screen size and eye, neck, shoulder, arm,Rizwan K et al The Healer Journal | Feburary Issue | Volume 3 -Issue 2 | Pg. 381…”
mentioning
confidence: 94%